Prognostic Value Of Chemotherapy-Induced Neutropenia In Metastatic Colorectal Cancer At Rsup Dr Sardjito Yogyakarta - Muhammad Ihsan Qomaruzzaman; Johan Kurnianda; Mardiah Suci Hardianti (Faculty of Medicine Universitas Gadjah Mada, 2016)
Background: Colorectal cancer is the third largest incidence of cancer in the world and is the third most common cause of death in women and men . Five-year overall survival (OS) in colorectal cancer who have undergone metastasis was 10 % . Hematologic toxicity may be a marker of biological activity of cytotoxic drug on various types of cancer . Neutropeniaafter chemotherapy known to be associated with increased patient survival .Objective : To establish whether chemotherapy-induced neutropenia is predictive of better outcome in patients with metastatic colorectal cancer (mCRC).Methods: This research was a case-control study. Subjects were patients with metastatic colorectal cancer in the Cancer Instalation Center Tulip RSUP dr. Sardjito who meet the inclusion and exclusion criteria. Data were analyzed by bivariate analysis using chi square test and multivariate analysis with logistic regression.Results: Neutropenia present in 26 patients (32.5%) of the total 80 patients of the study. Neutropenia were significantly affect OS ( p = 0.001 and OR 7.73, 95% CI: 2.51-23.80). Multivariate logistic regression analysis showed neutropenia and the number of metastases affect OS with p <0.001 and p <0.003.Conclusion: Neutropenia occurring during the two first lines of chemotherapy for metastases colorectal cancer is associated with better survival. Variables that affect OS is the number of metastases and incidence of neutropenia after chemotherapy.